Shifting the tax burden from labor to property: The case of Germany - Jörg Paetzold; Markus Tiefenbacher (University of Salzburg, Department of Social Sciences and Economics, 2016)
Contrary to frequent recommendations of the public finance literature and international institutions, a persistently high tax wedge on labor is observed in Europe. At the same time, the scope for shifting taxes from labor to more growth-friendly revenue sources appears underused in many European countries. This motivates our simulation of a revenue-neutral property tax reform for Germany, a country in which tax receipts from land are particularly low. More precisely, we assess by how much social insurance contributions (SIC) can be reduced when Germany switches from its current property tax scheme based on outdated cadastral values to one based on market property values. In order to make such a simulation possible, we match property related information with the input dataset of EUROMOD, the tax-benefit simulation model for the EU. Our results suggest that the implicit tax rate on labor could be reduced from currently 37,2% to 36,5%. Furthermore, we simulate different scenarios of the SIC reduction. Redistributive effects of these different scenarios tend to be modest and depend crucially on the design of the SIC reduction.
Keywords: D31; C15; H12; R28; C83; 330; Statistical Matching; Labor Tax; Property Tax; EUROMOD